Meningioma mimics: five key imaging features to differentiate them from meningiomas. Issue 9 (September 2017) - Starr, C.J.; Cha, S.
Abstract : There are a wide variety of intracranial mass lesions, both benign and malignant, which can closely mimic meningioma on imaging. We present five characteristic imaging features that can alert the radiologist to consider other differential diagnoses. Of the five imaging characteristics that were rarely seen in meningiomas, but common and specific for meningioma mimics, absence of dural tail is the most common (83.7%). Homogeneous T2 hyperintensity or T2 hypointensity are seen in nearly half of meningioma mimics and osseous destruction and leptomeningeal extension are present in 40.5% and 21.6% of meningioma mimics, respectively. The distinction between meningioma and its mimics is important because a large portion of the meningioma mimics requires substantially different clinical and surgical management. Highlights: Distinguishing mimics from meningiomas is difficult. However, it is essential, as management can greatly differ. Five key imaging features can help radiologists differentiate mimics from meningiomas. These include: marked T2 hypo- or hyperintensity, osseous destruction, leptomeningeal extension, and lack of dural tail.